1975
DOI: 10.1017/s0003356100035261
|View full text |Cite
|
Sign up to set email alerts
|

The response of lactating sows and their litters to different dietary energy allowances. 2. Weight changes and carcass composition of sows

Abstract: The live-weight changes of 48 sows were recorded over three reproductive cycles. All sows were given standard amounts of feed in gestation and one of four energy allowances during lactation. The daily intakes of digestible energy during lactation ranged from 12-2 to 18-2 Meal in the first, 12-9 to 19-6 Meal in the second and 13-2 to 20-2 Meal in the third lactation. Weight change in lactation responded to energy intake; sows on the lowest energy intake lost weight whilst those on the highest intake gained. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 7 publications
5
16
0
1
Order By: Relevance
“…As expected, sows fed Lo lost more (P<.01) weight during lactation than those fed Hi. These results agree with those of Elsley et al (1968), O'Grady et al (1975) and Reese et al (1982). Average litter size at weaning was not affected by energy intake which also agrees with previous reports (Elslcy et al, 1968;O'Grady et al, 1973;Reese et al, 1982).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As expected, sows fed Lo lost more (P<.01) weight during lactation than those fed Hi. These results agree with those of Elsley et al (1968), O'Grady et al (1975) and Reese et al (1982). Average litter size at weaning was not affected by energy intake which also agrees with previous reports (Elslcy et al, 1968;O'Grady et al, 1973;Reese et al, 1982).…”
Section: Resultssupporting
confidence: 93%
“…Apparently sows fed Lo compensated for their greater weight loss during Lac 1 [indicated by the differences (P<.01) in Lac 1 sow weaning weight]. Previous reports indicate that energy intake (Elsley et al, 1968;Adam and Shearer, 1975;O'Grady et al, 1975) and feed intake (Lodge et al, 1961;Elsley et al, 1969;Hitchcock et al, 1971) during lactation had no effect on net sow weight change during gestation. However, MacPherson et al (1969) and O'Grady (1971) reported that sows fed low protein diets during lactation tended to compensate by gaining more weight during the following gestation than those fed higher protein diets.…”
Section: Resultsmentioning
confidence: 94%
“…In this study, the HND diet was achieved by adding ,6% palm oil. Supplementary dietary fat fed to sows during lactation has been found to increase milk energy by increasing the fat content of the milk (O'Grady et al, 1973;Babinszky 1998). The current findings indicate that feeding a HND diet to sows during late gestation and lactation results in increased energy intake during this time period.…”
Section: Discussionmentioning
confidence: 99%
“…Tables 12 and 13 Mean values for percent fat, protein and lactose in this study are similar to those reported by Schuld and Bowland (1968). O'Grady et al (1973) found similar values for percent protein and lower levels for percent fat and lactose. and Rook and Witter (1968) reported lower values for percent lactose and higher percentages for fat and protein.…”
Section: Main Effectssupporting
confidence: 87%
“…reported that milk from first litter gilts was higher in lactose percent and lower in percent fat and protein. O'Grady et al (1973) found that milk from first litter gilts on day 24 of lactation was slightly higher in percent fat and protein and nearly equal in percent lactose and total solids when com pared to second parity sows. reported that milk from second parity sows was lower in percent fat and nearly equal in percent protein to that of first litter gilts.…”
Section: Milk Compositionmentioning
confidence: 93%